Abortion, the Irish Constitution, and constitutional change - Kenny, David (Revista de Investigações Constitucionais, 2018)
Abortion in Ireland is regulated by a constitutional provision that was inserted following a referendum in 1983. In May 2018, the Irish people, will voted to remove this provision from the Irish Constitution. In this paper, I examine the reasons for the insertion of the provision; the problems that emerged with it over time; the factors that motivated the campaign for change; and the gradual process of negotiating a proposed change within the political system. The paper concludes by drawing general lessons that might be derived about the about the costs and consequences of the Irish experience of making abortion into a matter of constitutional law and debating its removal. Though somewhat effective in blocking political opponents, constitutionalising abortion has had unexpected consequences: creating uncertainty; involving the judiciary in the regulation of abortion; and perhaps creating a tendency to elevate social and political issues to the constitutional level.